On the Problem of Study of Polish Influence upon the Russian Language in the 16th-18th cc. - Гарбулъ, Л.П. (Kalbotyra, 1985)
The article provides a review of investigations on the Polish-Russian linguistic contacts in the 16th–18th cc. These investigations have resulted in a big volume of “slovnik’s” polonisms. However, it is evident that due to cultural-historical and linguistic situalion in Moscow Russia the character of Polish influence upon the Russian language underwent changes. It is therefore not enough to state the presence of polonisms, what is more it is necessary to determine the functional peculiarities of Polish loan-words in the system of the language of Moscow Russia in the 16th–18th centuries.